Heat transfer characteristics and boiling heat transfer performance of novel Ag/ZnO hybrid nanofluid using free surface jet impingement. Issue 6 (19th September 2021) - Barewar, Surendra D.; Chougule, Sandesh S.
ABSTRACT: An experimental study has been performed to analyze the heat transfer characteristics by impinging a hybrid nanofluid jet on horizontal-heated test surface. The Ag/ZnO nanoparticles are synthesized and dispersed in DI water Φ = 0.02% to 0.1% by volume. A set of experiments were performed to calculate heat transfer coefficient and boiling performance at varying Reynolds numbers ranging from 1769 to 8273 and different ratios of H/D. The experimental analysis reveals that there is 88.53% and 87.17% improvement in the heat transfer coefficient and boiling performance for Ag/ZnO hybrid nanofluid when it is compared with water at H/D = 3.5.